CO2 enhances productivity, alters species composition, and reduces digestibility of Shortgrass Steppe vegetation - Morgan, Jack A., author; Mosier, Arvin R., author; Milchunas, Daniel G., author; LeCain, Daniel R., author; Nelson, Jim A., author; Parton, William J., author; Ecological Society of America, publisher (Colorado State University. Libraries, 2004)
The impact of increasing atmospheric CO2 concentrations has been studied in a number of field experiments, but little information exists on the response of semiarid rangelands to CO2, or on the consequences for forage quality. This study was initiated to study the CO2 response of the shortgrass steppe, an important semiarid grassland on the western edge of the North American Great Plains, used extensively for livestock grazing. The experiment was conducted for five years on native vegetation at the USDA-ARS Central Plains Experimental Range in northeastern Colorado, USA. Three perennial grasses dominate the study site, Bouteloua gracilis, a C4 grass, and two C3 grasses, Pascopyrum smithii and Stipa comata. The three species comprise 88% of the aboveground phytomass. To evaluate responses to rising atmospheric CO2, we utilized six open-top chambers, three with ambient air and three with air CO2 enriched to 720 mmol/mol, as well as three unchambered controls. We found that elevated CO2 enhanced production of the shortgrass steppe throughout the study, with 41% greater aboveground phytomass harvested annually in elevated compared to ambient plots. The CO2-induced production response was driven by a single species, S. comata, and was due in part to greater seedling recruitment. The result was species movement toward a composition more typical of the mixed-grass prairie. Growth under elevated CO2 reduced the digestibility of all three dominant grass species. Digestibility was also lowest in the only species to exhibit a CO2-induced production enhancement, S. comata. The results suggest that rising atmospheric CO2 may enhance production of lower quality forage and a species composition shift toward a greater C3 component.
Keywords: C4; C3; carbon dioxide (CO2); digestibility; forage quality; global change; grassland; recruitment; Bouteloua gracilis; Pascopyrum smithii; Stipa comata